2020
DOI: 10.1093/jac/dkaa115
|View full text |Cite
|
Sign up to set email alerts
|

Global clonal spread of mcr-3-carrying MDR ST34 Salmonella enterica serotype Typhimurium and monophasic 1,4,[5],12:i:− variants from clinical isolates

Abstract: Objectives To investigate the prevalence and transmission of mcr-3 among Salmonella enterica serotype Typhimurium and 1,4,[5],12:i:−. Methods A total of 4724 clinical Salmonella isolates were screened for the presence of mcr-3 in China during 2014–19. The clonal relationship of the mcr-3-positive isolates and their plasmid contents and complete sequence were also characterized based on WGS data from the Illumina and MinION pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 38 publications
6
34
0
Order By: Relevance
“…Thus, it should be noted that the mcr gene, especially mcr-3.1 , has already spread in Thailand since at least 2007, the earliest isolation time point of the mcr -harbouring isolates among our collection of Salmonella clinical isolates. Currently, the mcr-3 gene has become more widespread and prevalent in Salmonella , S. Typhimurium, and a monophasic variant of S. Typhimurium in particular 21 , 24 , 25 . The clonal spread of the MDR ST34 S. Typhimurium (including monophasic variants) was observed in China during 2014–2019, during which time the global distribution was confirmed by the high similarity between the genomes of mcr-3 -harboring Salmonella isolated from across four continents 25 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it should be noted that the mcr gene, especially mcr-3.1 , has already spread in Thailand since at least 2007, the earliest isolation time point of the mcr -harbouring isolates among our collection of Salmonella clinical isolates. Currently, the mcr-3 gene has become more widespread and prevalent in Salmonella , S. Typhimurium, and a monophasic variant of S. Typhimurium in particular 21 , 24 , 25 . The clonal spread of the MDR ST34 S. Typhimurium (including monophasic variants) was observed in China during 2014–2019, during which time the global distribution was confirmed by the high similarity between the genomes of mcr-3 -harboring Salmonella isolated from across four continents 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the mcr-3 gene has become more widespread and prevalent in Salmonella , S. Typhimurium, and a monophasic variant of S. Typhimurium in particular 21 , 24 , 25 . The clonal spread of the MDR ST34 S. Typhimurium (including monophasic variants) was observed in China during 2014–2019, during which time the global distribution was confirmed by the high similarity between the genomes of mcr-3 -harboring Salmonella isolated from across four continents 25 . Interestingly, most patients with mcr-3 -positive Salmonella infections from Denmark, Canada, USA, and Australia had a travel history to Thailand, Vietnam, or China, during 2013–2016 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the ASSuT tetra-(ampicillin, streptomycin, sulfonamides, and tetracycline) and ACSSuT (ampicillin, chloramphenicol, streptomycin, sulfonamides, and tetracycline) penta-resistant patterns are the most commonly reported (Mellor et al, 2019;Thung et al, 2016;Wang et al, 2019). Salmonella 4, [5],12:i:-, a monophasic variant of Salmonella Typhimurium, progressively became an emerging multidrug resistant clade carrying plasmid-mediated resistance genes (Elnekave et al, 2018;Mourao et al, 2014) and the sequence types mostly are ST19 and ST34 (Elnekave et al, 2018;Pernille Gymoese et al, 2017;Sun et al, 2020). The antimicrobial resistance (AMR) of Salmonella has become a matter of concern worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…After Salmonella species carrying mcr-1 were detected in the United Kingdom in 2016, the level of occurrence of mcr-1 in Salmonella among livestock and humans, but also the environment, is increasing worldwide (Cui et al, 2017;Yi et al, 2017b). In addition, although another five mcr variants (mcr-2, mcr-3, mcr-4, mcr-5, and mcr-9) have been identified in Salmonella species (Carattoli et al, 2018;Garcia-Graells et al, 2018;Borowiak et al, 2019;Carroll et al, 2019;Sun et al, 2020), mcr-1 is still the most common mcr gene found in COL-resistant Salmonella spp. (Borowiak et al, 2020).…”
Section: Introductionmentioning
confidence: 99%